Comparing Digital Phase-Locked Loop and Kalman Filter for Clock Tracking in Ultrawideband Location System - Qian Gao; Chong Shen; Kun Zhang (Journal of Electrical and Computer Engineering)
For timing and synchronization system, digital phase-locked loop (DPLL) and Kalman filter all have been widely used as the clock tracking and clock correction schemes for the similar structure and properties. This paper compares the two schemes used for ultrawideband (UWB) location system. The improved Kalman filter is more immune to interference.